The Importance Of The Subject "Art Photo Composition" In The Study Of Photo Art - Jasur Jumaev (The American Journal of Social Science and Education Innovations, 2021)
The article covers the basic concepts of artistic photo composition, the general purpose of the composition, the artist's use of visual and expressive means of this art, the use of specific methods and techniques of constructive construction.